Teachers' Experiences of Teaching as Inquiry and Biculturally Responsive Pedagogy for Māori Students in Schools with a Low Percentage of Māori Students - Kendall, Lara (Auckland University of Technology, 2019)
Historical marginalisation and deficit theory toward the Māori people in Aotearoa New Zealand schools has resulted in Government expectations for teachers to improve outcomes for Māori students. This research aimed to critically examine teachers’ experiences of teaching as inquiry and biculturally responsive pedagogy for Māori students in schools with a low percentage of Māori students. Teachers in schools with diverse, multicultural communities should uphold the fundamental principles of the Treaty of Waitangi. Bicultural responsivity in teaching and learning has been a Government priority for decades. However, the variance in student educational outcomes is still heavily weighed against Māori students in comparison with their non-Māori peers. Historically, teachers have been required to solve the problem of the education gap, but with little effect. Teachers are expected to inquire into the action and reflection of teaching and learning, to change and improve teaching practice. The application of teaching as inquiry and biculturally responsive pedagogy conjointly is convoluted and complicated. Although teaching as inquiry offers teachers the opportunity to reflect on effective practice, practitioners find it problematic to transpose policy into theory and theory into practice. The research methodology focused on a collective case study design. Findings were collated from semi-structured interviews, a questionnaire and document review. A review of relevant research literature supported the examination of the key themes that emerged from the data. The findings presented experiences and barriers to teaching and learning for teachers in schools with less than 10% Māori students. Three key themes were identified: values, beliefs and behaviours; the authenticity of practice; and leadership for teaching as inquiry and bicultural responsivity. The findings of this study identified the barriers and challenges experienced by the participants. Participants commented on the relational and cultural context of teaching in a bicultural setting, but not how to relate this to teaching as inquiry. Their collective experiences showed there was no direct pedagogical solution to supporting teaching to raise outcomes for Māori students. However, this research suggests that a system's response is necessary for the impactful inquiry into teaching and biculturally responsive pedagogy.
Keywords: Biculturally Responsive Pedagogy; Schools with a Low Percentage of Māori Students; Teaching as Inquiry; Marginalisation and deficit theory